2012
DOI: 10.1371/journal.pone.0043699
|View full text |Cite
|
Sign up to set email alerts
|

The Lethal Toxin from Australian Funnel-Web Spiders Is Encoded by an Intronless Gene

Abstract: Australian funnel-web spiders are generally considered the most dangerous spiders in the world, with envenomations from the Sydney funnel-web spider Atrax robustus resulting in at least 14 human fatalities prior to the introduction of an effective anti-venom in 1980. The clinical envenomation syndrome resulting from bites by Australian funnel-web spiders is due to a single 42-residue peptide known as δ-hexatoxin. This peptide delays the inactivation of voltage-gated sodium channels, which results in spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
0
12
0
2
Order By: Relevance
“…However, this would imply secondary loss of plant/fungi-type ICK peptides in animals, because animals and fungi form a monophyletic clade (Opisthokonta) with respect to plants (Plantae) [65]. Moreover, gene structure does not appear to be particularly well conserved in ICK-encoding genes since spider ICK toxins are encoded by genes that are either intronless [66] or have a variety of intron-exon architectures [67,68]. While gene structure alone does not provide strong support for multiple origins of the ICK fold, structural data do suggest it may have evolved twice.…”
Section: The Ick Fold May Have Evolved Twice In Eukaryotamentioning
confidence: 99%
“…However, this would imply secondary loss of plant/fungi-type ICK peptides in animals, because animals and fungi form a monophyletic clade (Opisthokonta) with respect to plants (Plantae) [65]. Moreover, gene structure does not appear to be particularly well conserved in ICK-encoding genes since spider ICK toxins are encoded by genes that are either intronless [66] or have a variety of intron-exon architectures [67,68]. While gene structure alone does not provide strong support for multiple origins of the ICK fold, structural data do suggest it may have evolved twice.…”
Section: The Ick Fold May Have Evolved Twice In Eukaryotamentioning
confidence: 99%
“…A search of the recently published genome of the velvet spider Stegodyphus mimosarum (Araneomorphae) (Sanggaard et al, 2014), revealed an ITP/CHH-like gene (Genbank: AZAQ01021694.1) containing an unusually large intron ($9.7 kb) in the same position within the mature peptide as in S. maritima. Moreover, unlike araneomorph spiders (Krapcho et al, 1995), mygalomorphs appear to express intronless toxin genes Pineda et al, 2012;Tang et al, 2010), possibly indicating an inability to splice transcripts expressed in the toxin-producing regions of the venom gland.…”
Section: Figure 5 Timeline Of Chh/itp and Hand Toxin Recruitmentsmentioning
confidence: 99%
“…For some spider species, silk (Prosdocimi et al ., ) and venom gland (Kozlov et al ., ; Quintero‐Hernandez et al ., ) transcriptome data are available; however, no full spider genome has been sequenced yet. The majority of short spider toxin genes known to date do not contain introns (Qiao et al ., ; Tang et al ., ; Pineda et al ., ). As for two‐domain spider toxins, we have recently reported the structure of OlTx toxin genes from Oxyopes lineatus , which were also found to be intronless (Sachkova et al ., ).…”
Section: Introductionmentioning
confidence: 97%